2021
DOI: 10.1002/uog.23754
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of transvaginal sonography for detecting parametrial involvement in women with deep endometriosis: systematic review and meta‐analysis

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
(125 reference statements)
3
27
1
Order By: Relevance
“…It remains to be seen whether the TVS sliding sign test performs equally well and is reproducible in the hands of less experienced examiners. The findings of this meta‐analysis confirm the fundamental role of TVS as a diagnostic tool in women with suspected endometriosis, suggested by previous studies 40–42 .…”
Section: Discussionsupporting
confidence: 88%
“…It remains to be seen whether the TVS sliding sign test performs equally well and is reproducible in the hands of less experienced examiners. The findings of this meta‐analysis confirm the fundamental role of TVS as a diagnostic tool in women with suspected endometriosis, suggested by previous studies 40–42 .…”
Section: Discussionsupporting
confidence: 88%
“…The diagnosis is limited to those undergoing laparoscopy and this clinical decision is based on a variable mixture of clinical exams and symptoms and imaging. The accuracies of imaging as ultrasound or MRI are well described (78,79), but the predictive values vary with the locally variable prevalences, and their importance in clinical decision making varies from little (58,76) to very much (80). Not only the indication for laparoscopy is variable also the recognition of endometriosis (81) as demonstrated for subtle lesions and observed for deep and appendiceal endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Parametrial endometriosis involvement occurs more frequently in patients with severe endometriosis, possibly with hypogastric/sacral plexus or sciatic nerve involvement [ 34 , 35 ]. In a recent meta-analysis, Guerriero et al [ 36 ] found that in the detection of endometriosis in the parametrium, the sensitivity and specificity are 31% and 98%, respectively. This low sensitivity can be explained by the fact that specific training is needed to properly visualize this anatomical area [ 36 ].…”
Section: Transvaginal Ultrasoundmentioning
confidence: 99%
“…In a recent meta-analysis, Guerriero et al [ 36 ] found that in the detection of endometriosis in the parametrium, the sensitivity and specificity are 31% and 98%, respectively. This low sensitivity can be explained by the fact that specific training is needed to properly visualize this anatomical area [ 36 ]. Assessing the USL might suggest a thorough evaluation of the parametrium [ 37 ].…”
Section: Transvaginal Ultrasoundmentioning
confidence: 99%